2020
DOI: 10.1002/jssc.202000372
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the enantioselective interaction between selected drug enantiomers and human serum albumin by mobility shift‐affinity capillary electrophoresis

Abstract: Mobility shift-affinity capillary electrophoresis was employed for enantioseparation and simultaneous binding constant determination. Human serum albumin was used as a chiral selector in the background electrolyte composed of 20 mM phosphate buffer, pH 7.4. The applied setup supports a high mobility shift since albumin and the drug-albumin complex hold negative net charges, while model compounds of amlodipine and verapamil are positively charged. In order to have an accurate effective mobility determination, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…Table 5 showed different studies that have been reported over the years for the evaluation of the binding affinity of HSA of numerous drugs and other bioactive compounds using CE techniques. Many studies focused on the individual binding parameters for each compound/enantiomer [153,155,161] while others also described competitive studies between compounds to the binding sites of HSA [156,157,159]. Furthermore, most of these studies were enantioselective studies where the differences in binding of each enantiomer of the analyzed compounds to HSA were evaluated and compared using, many of them, HSA as a chiral selector [150,152,154,155].…”
Section: Capillary Electrophoresismentioning
confidence: 99%
See 1 more Smart Citation
“…Table 5 showed different studies that have been reported over the years for the evaluation of the binding affinity of HSA of numerous drugs and other bioactive compounds using CE techniques. Many studies focused on the individual binding parameters for each compound/enantiomer [153,155,161] while others also described competitive studies between compounds to the binding sites of HSA [156,157,159]. Furthermore, most of these studies were enantioselective studies where the differences in binding of each enantiomer of the analyzed compounds to HSA were evaluated and compared using, many of them, HSA as a chiral selector [150,152,154,155].…”
Section: Capillary Electrophoresismentioning
confidence: 99%
“…Many studies focused on the individual binding parameters for each compound/enantiomer [153,155,161] while others also described competitive studies between compounds to the binding sites of HSA [156,157,159]. Furthermore, most of these studies were enantioselective studies where the differences in binding of each enantiomer of the analyzed compounds to HSA were evaluated and compared using, many of them, HSA as a chiral selector [150,152,154,155]. However, a few studies used cyclodextrins for this purpose while HSA was incubated with the samples before the analysis [151,153,161,162].…”
Section: Capillary Electrophoresismentioning
confidence: 99%
“…The preferable interactions of the ( R )-enantiomer of ibuprofen with HSA causes a greater proportion of the ( S )-enantiomer in free form. Investigation of the enantioselective interaction of verapamil and amlodipine with HSA showed that ( R )-(+)-verapamil has stronger bind to HSA compared to ( S )-(-)-verapamil, while ( S )-(-)-amlodipine has a stronger bind than the ( R) -enantiomer [ 26 ]. In another study, the binding of ( S )-omeprazole (esomeprazole) and ( R )-enantiomer to HSA, under simulated physiological conditions, demonstrated that ( R )-omeprazole had higher binding constants than ( S )-omeprazole [ 27 ].…”
Section: Enantioselectivity In Drug Pharmacokineticsmentioning
confidence: 99%
“…Proteins are still playing a particularly good role in investigating enantioselective protein interaction with enantiomeric drugs [ 81 ]. Ratih et al [ 7 ] used human serum albumin as a chiral selector in 20 mM phosphate buffer pH 7.4 for enantioseparation and simultaneous binding constant determination of amlodipine and verapamil enantiomers. It is worth noting that microscale thermophoresis [ 82 ] also is useful in the study of enantioselective affinity of chiral drugs toward therapeutic target proteins [ 83 ].…”
Section: Chiral Capillary Electrokinetic Chromatography Principle and Selectorsmentioning
confidence: 99%
“…Some counter enantiomers are recognized as being pharmacologically same active, less active, different active, inactive, antagonistic, or even toxic compared to their active enantiomeric pair. Distomer is considered the less potent, while the eutomer is more powerful for a particular action [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%